Restriction-modification systems and DNA methylation profile of Pectobacterium carotovorum 2A - Diubo, Yulia V.; Akhremchuk, Artur E.; Valentovich, Leonid N.; Nikolaichik, Yevgeny A. (Experimental Biology and Biotechnology, 2021)
The methylation profile of Pectobacterium carotovorum 2A genome was studied using the Oxford Nanopore sequencing technology. The specificity of the methylase subunits of the three restriction-modification systems of this strain was determined. Analysis of homologous systems showed the uniqueness of the type I restriction-modification system and the type IV restriction system specific to methylated DNA of this strain. The work confirms the applicability of Oxford Nanopore technology to the analysis of bacterial DNA modifications and is also the first example of such an analysis for Pectobacterium spp.
Keywords: Oxford Nanopore sequencing; methylation; restriction-modification system; N6-methyladenosine; 5-methylcytosine